Social Media Engagement, Attitudes towards Cancel Culture, and Brand Attitude: A Conceptual Framework - Banda, Tatenda; Haarhoff, Rene (International Review of Management and Marketing, 2026)
Cancel culture has become a powerful social movement shaping Generation Z consumer behaviour, driven by public accountability practices such as shaming, withdrawing or boycotting entities perceived to have violated social norms. Although scholarship on digital activism and consumer behaviour has expanded, conceptual clarity remains limited in explaining how social media engagement shapes attitudes toward cancel culture and how participation in cancel culture affects brand evaluations. This conceptual paper addresses these gaps by advancing a theoretical framework that theorises the sequential pathway: social media engagement → attitudes toward cancel culture → participation → brand attitude. The framework integrates the Theory of Planned Behaviour (TPB) and Social Influence Theory (SIT) as its core foundations. Two moderating conditions are specified: self-identity in the engagement–attitude link and perceived influencer credibility in the participation–brand attitude link. Systems thinking is acknowledged as a meta-theoretical perspective but not positioned as a core framework; Cognitive Dissonance Theory and Generational Cohort Theory are treated as contextual references. The paper contributes to literature by offering a parsimonious conceptual model of social-media-driven consumer behaviour and by highlighting practical insights into reputational risk management in digital brand ecosystems. This study contributes by: (i) advancing a theoretically grounded framework linking social media engagement, attitudes towards cancel culture, and brand attitude through TPB and SIT; (ii) specifying two boundary conditions, self-identity and perceived influencer credibility that moderate these relationships; and (iii) establishing a foundation for empirical testing of cancel-culture dynamics in emerging-market contexts.